Bontang Mangrove Park Development Strategy In Kutai National Park Using GSTC-D - Hana Gloria Ford Hutagalung; Pandu Kusumoputro Utomo; Ali Suhardiman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Mangrove ecotourism requires a balance between environmental protection and sustainable destination management. However, the use of the Global Sustainable Tourism Council Destination Criteria (GSTC-D) for development planning remains limited. This study aims to assess the sustainability performance of the Bontang Mangrove Park in Kutai National Park and design guidelines based on identified sustainability gaps. A descriptive qualitative approach was employed, utilizing field observations, semi-structured interviews with stakeholders, document review, and a literature review. Sustainability performance was measured using a scoring system based on GSTC-D indicators, which include sustainable management, socio-economic sustainability, cultural sustainability, and environmental sustainability. The evaluation found that 70 indicators were fully met (45.75%), 36 were partially met (23.52%), and 47 were not met (30.71%). Furthermore, 21 indicators were marked as not applicable due to destination characteristics. The main deficiencies were in waste management, energy conservation, water use, accessibility, visitor management, and environmental education. These gaps were translated into recommendations for development, such as an inclusive circulation system, improved utility infrastructure, interpretation facilities, and a sustainable site management strategy. The findings indicate that Bontang Mangrove Park has great potential to become a sustainable ecotourism destination, but requires better management and infrastructure to meet GSTC-D standards. This study is unique in that it expands the use of GSTC-D beyond simply assessing sustainability by developing specific design guidelines for mangrove ecotourism based on the evaluation results.